Peer-group support intervention improves the psychosocial well-being of AIDS orphans: Cluster randomized trial - Kumakech, Edward; Cantor-Graae, Elizabeth; Maling, Samuel; Bajunirwe, Francis (Social science & medicine, 2009)
Accumulating evidence suggests that AIDS orphanhood status is accompanied by increased levels of psychological distress such as anxiety, depression, intense guilt, shame, and anger. However, few studies have examined the possible reduction of psychological distress in AIDS orphans through the help of interventions that promote well-being. The objective of the study was to evaluate the effects of a school-based peer-group support intervention combined with periodic somatic health assessments and treatment on the psychosocial well-being of AIDS orphans in the Mbarara District of southwestern Uganda. In a cluster randomized controlled design, 326 AIDS orphans aged 10–15 years were assigned to either peer-group support intervention combined with monthly somatic healthcare (n = 159) or control group (n = 167) for follow-up assessment. Baseline and 10 week follow-up psychological assessments were conducted in both groups using self-administered Beck Youth Inventories. Complete data were available for 298 orphans. After adjusting for baseline scores, follow-up scores for the intervention group in comparison with controls showed significant improvement in depression, anger, and anxiety but not for self-concept. This study demonstrated that peer-group support intervention decreased psychological distress, particularly symptoms of depression, anxiety and anger. Thus, the use of peer-group support interventions should be incorporated into existing school health programs.
Keywords: AIDSOrphansPeer-group supportInterventionPsychological distressUgandaSchools